ANALISIS KEMAMPUAN SISWA DALAM PENGGUNAAN BAHASA BAKU DAN TIDAK BAKU SESUAI DENGAN EJAAN YANG TELAH DISEMPURNAKAN (EYD) - Arozatulo Bawamenewi; David Angelus Emanuel Laia (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to analyze students' abilities in using standard and non-standard language according to Enhanced Spelling (EYD). In the current era of globalization, good and correct use of Indonesian is very important to maintain cultural richness and national identity. The research population involved all class VIII students at SMP Negeri 5 Botomuzei, namely 32 people, based on sample criteria (stratified random sampling) there were 25 people. The research method used is descriptive quantitative with data collection through written tests and interviews. The independent variable is students' understanding of EYD while the dependent variable is the ability to use standard and non-standard language. EYD as an official spelling guide, plays a very vital role in maintaining the consistency and quality of the Indonesian language, as well as supporting efforts to preserve and develop the language as a national identity. The research results show that the majority of students have a fairly good understanding of the EYD rules, but still often make mistakes in the application of standard and non-standard language in written and spoken contexts. Factors that influence students' abilities include the social environment, mass media, and daily language habits. This research concludes that there is a need to increase awareness and more intensive learning regarding the use of standard and non-standard language according to EYD among students. The recommendations given are improving the quality of Indonesian language teaching in schools as well as providing learning materials that are more interactive and relevant to current developments. As well as increasing awareness of the importance of using standard words.